The In Vivo Transcriptomic Blueprint of Mycobacterium tuberculosis in the Lung - Coppola, Mariateresa; Lai, Rachel P-J.; Wilkinson, Robert J.; Ottenhoff, Tom H. M. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (Mtb) genes encoding proteins targeted by vaccines and drugs should be expressed in the lung, the main organ affected by Mtb, for these to be effective. However, the pulmonary expression of most Mtb genes and their proteins remains poorly characterized. The aim of this study is to fill this knowledge gap. We analyzed large scale transcriptomic datasets from specimens of Mtb-infected humans, TB-hypersusceptible (C3H/FeJ) and TB-resistant (C57BL/6J) mice and compared data to in vitro cultured Mtb gene-expression profiles. Results revealed high concordance in the most abundantly in vivo expressed genes between pulmonary Mtb transcriptomes from different datasets and different species. As expected, this contrasted with a lower correlation found with the highest expressed Mtb genes from in vitro datasets. Among the most consistently and highly in vivo expressed genes, 35 have not yet been explored as targets for vaccination or treatment. More than half of these genes are involved in protein synthesis or metabolic pathways. This first lung-oriented multi-study analysis of the in vivo expressed Mtb-transcriptome provides essential data that considerably increase our understanding of pulmonary TB infection biology, and identifies novel molecules for target-based TB-vaccine and drug development.